Initial atmospheric corrosion studies of copper from macroscale to nanoscale in a simulated indoor atmospheric environment. (February 2022) - Zhao, Weijie; Babu, R. Prasath; Chang, Tingru; Odnevall, Inger; Hedström, Peter; Johnson, C. Magnus; Leygraf, Christofer
Abstract: Corrosion effects on copper exposed in a humid atmosphere with formic acid (mimicking indoor corrosion) have been explored through successive increase in surface lateral resolution from macroscale (IRRAS, GIXRD) over microscale (LOM, SEM, IR microscopy) to nanoscale (Nano-FTIR, FIB/SEM/EDS). Initial more uniform growth of Cu2 O is followed by more varying topography and thickness until local removal of Cu2 O enables the aqueous adlayer to react with the copper substrate. Local formation of Cu(OH)(HCOO) and adjacent Cu2 O provide microscopic and spectroscopic evidence of corrosion cells. Nano-FTIR shows that the density of Cu(OH)(HCOO) nuclei, but not their size, increases with exposure time. Graphical abstract: ga1 Highlights: Corrosion effects on copper explored at the macroscale, microscale, and nanoscale levels. Techniques include IRRAS, GIXRD, LOM, SEM, IR microscopy, Nano-FTIR, and FIB/SEM/EDS. Coherent mechanistic picture obtained from all techniques. Nanoscale images and distribution of Cu(OH)(HCOO) nuclei visualised with Nano-FTIR. Direct microscopic and spectroscopic evidence of corrosion cells.